Pedagogical conditions of professional training for future programmer engineers - Romanovskyi, O. G.; Goncharenko, T. Y. (НТУ "ХПІ", 2017)
The problem of professional training of future engineers-engineers in the technical university is studied. It is considered the implementation of pedagogical conditions that contribute to the improvement of this training. The ways of introduction of the offered pedagogical conditions in the process of professional training of students are offered.

Досліджується проблема професійної підготовки майбутніх інженерів-програмістів в технічному університеті. Розглядається реалізація педагогічних умов, що сприяють удосконаленню цієї підготовки. Пропонуються шляхи впровадження запропонованих педагогічних умов у процес професійної підготовки студентів.
Педагогічні умови професійної підготовки майбутніх інженерів-програмістів
Keywords: vocational training; engineers-programmers; activation of students; dual approach; інженери-програмісти; активізація студентів; дуальний підхід